(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The disease conditions that people suffer from, which caused disease, have been alleviated by the emergence of industrial treatment techniques, and this happened due to technological development. Many lives have been saved by the artificial pancreas technology. In addition, because the pancreas is important in the process of transplantation, it has become an industrial alternative for people who have type 1 diabetes. In this paper, we will discuss a comparative study of the types of pancreas. After mentioning an introduction to the pancreas transplantation, as well as an introduction to the history of an artificial pancreas in this paper. We talked about the types of artificial pancreas and presented the most important. Specifications for each type. We also made a recommendation on the best available ones that are suitable for everyday use. Finally, we looked at a prospective study on the possibility of developing an artificial pancreas